Parques urbanos e biofilia: uma avaliação das tendências científicas e de seus aspectos no município de Campo Grande - MS - Nádia Mattos Melo (2023)
The development of cities is a historical process that has gained strength in recent decades, and that has been occurring in a disorderly and accelerated way. Cities must take into account the maintenance of natural environments to promote quality of life, which can occur in urban parks. Green areas bring the population closer to nature. These spaces are very attractive and when they offer quality, they tend to bring benefits to the user population. Urban parks are not just for contemplation of nature, they are home to fauna and flora and considered an important element within cities. In addition to offering well-being, they can contribute to combating pollution, maintaining biodiversity, collaborating with environmental conservation and helping to control the region's temperatures, which reduces heat islands. Urban parks, in addition to contributing in all the aforementioned aspects, also collaborate in the perception of biophilia, as they promote the integration of man with nature. This project is organized into two chapters in the form of an article and has as main objectives: 1) to identify with a bibliometric study, trends in scientific research addressing the theme urban parks, biophilia and environmental perception and 2) to observe aspects of biophilia in urban parks de Campo Grande – MS and the perception of biophilia by park users and their importance. The results presented showed that, in general, studies focused on urban parks, biophilia and environmental perception have increased in the last ten years with a significant number of publications on urban spaces and green areas, as the need for external environments has increased. shown to be necessary in large centers. It was concluded that the urban parks of Campo Grande - MS offer most of the aspects and characteristics of biophilia described and presented by several authors. The data discussed in this research corroborate with several studies that the presence of biophilia brings numerous benefits to the user population, offering health, well-being and quality of life, not only to the population, but to the entire city. Keywords: Environmental Planning, Environmental Perception. Green Areas, Landscaping, Urban Planning.